The effects of hybrid physical activity program on various motor skills in primary school children - Mehmet Batın Bayburtlu; Ayça Genç; Fatma Ünal (IP Iermakov S.S., 2024)
Background and Study Aim. Physical activity in children is fundamental to the development of motor skills. Despite its importance, physical activity programs do not fully address the needs of this age group. This study examined the effects of a hybrid physical activity program on specific motor skills in primary school children. Material and Methods. A quantitative single-group pretest-posttest model was used in this study. The research group included 34 voluntary students, with 19 boys and 15 girls, all in the 3rd and 4th grades of primary school. Participants followed a hybrid physical activity program developed by the researcher. The program lasted for 8 weeks, with sessions conducted 3 days a week face-to-face and 4 days a week at home. Home sessions involved parental support through the Moodle system, using educational videos or visual games. Each session lasted one hour and was supervised by an expert trainer. Motor competence data were collected using the second version of the "Test of Gross Motor Development-2" (TGMD-2), known for its reliability and validity. The data were analyzed using the SPSS 26.0 statistical package, with a significance level set at p<0.05. Results. The study's findings showed significant differences in some sub-skills and total raw scores of the locomotor and object control tests between boys and girls (p < 0.05). Significant differences were also found between the 8- and 9-year-old groups in sub-skills and total raw scores (p < 0.05). Additionally, a significant difference was observed in certain sub-skills and total raw score assessments between the 3rd and 4th grades (p < 0.05). Conclusions. The hybrid physical activity program proved to be an effective approach for enhancing motor skills in primary school children. The findings highlight the importance of tailored physical activity programs that consider individual characteristics such as age, gender, and grade level. Implementing such programs in both school and home settings can promote more comprehensive motor development in children.